Hubungan Fungsi Kognitif dengan Tingkat Kemandirian pada Lansia - Tia Ayu Adiningsih; Tri Wahyuningsih; Mohamad Anwar (Universitas Malahayati Lampung, 2022)
ABSTRACT : THE CORRELATION OF COGNITIVE FUNCTION WITH THE LEVEL OF INDEPENDENCE OF THE ELDERLY Introduction: The increasing of elderly population will increase new problems in various fields. Some problems and disorders that often arise or occur in the elderly are decreased of cognitive function. The physical changes that have decreased will cause various life aspects interference that have big influence on the level of independence of the elderly, include the decline in cognitive function. The results of research that have been developed by several experts suggest that 50% of elderly with cognitive impairment will feel dependence on their caregiver or closest companion such as the family. Objective: This research was to analyze the correlation between cognitive function and the level of independence of the elderly at RW 14 Public Health Center Cibeber.Methods: The research used an analytical survey with a cross sectional approach. The sample in this research amounted to 88 respondents using purposive sampling technique. The data collection use the results of interview with the Mini-Mental State Exam (MMSE) and the Katz Index. Analysis of Kolmogorof-Smirnov test data using SPSS results. Results: The results of this research were obtained with the results of the MMSE interview, most of (60.2%) of elderly had normal cognitive function, most of (64.8%) of elderly had a level of independence. The results of the analysis obtained (p value = 0.000 (0.005) it means that there is a correlation between the two variables.Conclusion: There is a correlation between the cognitive function of the elderly and the level of independence in the elderly at RW 14 Public Health Center of Cibeber Area. The family is expected to be able to prevent or reduce the impact of physical decline and psychology in the elderly. Keywords: Elderly, Cognitive Function, Level of Independence. INTISARI: HUBUNGAN FUNGSI KOGNITIF DENGAN TINGKAT KEMANDIRIAN PADA LANSIA Pendahuluan: Semakin meningkatnya populasi lanjut usia maka akan meningkatkan masalah baru diberbagai bidang. Beberapa masalah dan gangguan yang sering muncul atau terjadi pada lansia adalah menurunnya fungsi kognitif. Perubahan fisik yang cenderung mengalami penurunan akan menyebabkan berbagai gangguan aspek kehidupan yang mempunyai pengaruh besar dalam tingkat kemandirian lansia, termasuk dalam penurunan fungsi kognitif. Hasil penelitian yang telah dikembangkan oleh beberapa ahli mengemukakan bahwa 50% lansia yang mengalami gangguan kognitif akan mengalami ketergantungan terhadap caregiver atau pendamping terdekatnya yaitu pihak keluarga.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan fungsi kognitif dengan tingkat kemandirian lansia di wilayah Puskesmas Cibeber RW 14. Metode: Penelitian menggunakan survey analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 88 responden dengan menggunakan teknik purposive sampling. Pengumpulan data menggunakan hasil wawancara dengan Mini-Mental State Exam (MMSE) dan Katz Index. Analisa data uji Kolmogorof-Smirnov menggunakan hasil SPSS.Hasil: Hasil penelitian ini didapatkan dengan hasil wawancara MMSE sebagian besar (60,2%) memiliki fungsi kognitif normal, sebagian besar (64,8%) memiliki tingkat kemandirian mandiri. Hasil analisis didapatkan (p value = 0,000 α (0,005) artinya ada hubungan antara dua variabel tersebut.Kesimpulan: Terdapat hubungan antara fungsi kognitif lansia dengan tingkat kemandirian pada lansia di Wilayah Puskesmas Cibeber RW 14. Pihak keluarga diharapkan mampu melakukan pencegahan atau pengurangan dampak kemunduran fisik dan psikis pada lansia. Kata kunci : Lansia, Fungsi Kognitif, Tingkat Kemandirian